Del masoquismo y otros destinos de pulsión (2016)
ABSTRACT:This article makes part of a research carried out within the framework of the Master in Psychoanalytical Research, which comes up from the analysis of clinical material obtained from psychotherapeutic work developed during more than three years with children coming to a psychology service of a non-profit institution located in one of Medellin's communes, mainly because of problems related to child maltreatment. In order to obtain such analysis material, we started from the psychoanalytical thesis of psychic determinism and the neutrality of the therapist. For that reason we invited some kids to draw and associate freely, expecting what they showed would be related to their maltreatment experiences. Consequently, the methodology used consisted not only in handing over to children but in leading them to use drawing.